Population‐based birth defects data in the United States, 2011–2015: A focus on eye and ear defects. Issue 19 (16th November 2018) - Stallings, Erin B.; Isenburg, Jennifer L.; Mai, Cara T.; Liberman, Rebecca F.; Moore, Cynthia A.; Canfield, Mark A.; Salemi, Jason L.; Kirby, Russell S.; Short, Tyiesha D.; Nembhard, Wendy N.; Forestieri, Nina E.; Heinke, Dominique; et al.
Abstract: Background/Objectives: In this data brief, we examine major eye and ear anomalies (anophthalmia/microphthalmia, anotia/microtia, and congenital cataract) for a recent 5‐year birth cohort using data from 30 population‐based birth defects surveillance programs in the United States. Methods: As a special call for data for the 2018 NBDPN Annual Report, state programs reported expanded data on eye/ear anomalies for birth years 2011–2015. We calculated the combined overall prevalence (per 10, 000 live births) and 95% confidence intervals (CI), for the three anomalies as well as by maternal age, maternal race/ethnicity, infant sex, laterality, presence/absence of other major birth defects, and case ascertainment methodology utilized by the program (active vs. passive). Results: The overall prevalence estimate (per 10, 000 live births) was 1.5 (95% CI: 1.4–1.5) for anophthalmia/microphthalmia, 1.5 (95% CI: 1.4–1.6) for congenital cataract, and 1.8 (95% CI: 1.7–1.8) for anotia/microtia. Congenital cataract prevalence varied little by maternal race/ethnicity, infant sex, or case ascertainment methodology; prevalence differences were more apparent across strata for anophthalmia/microphthalmia and anotia/microtia. Prevalence among active vs. passive ascertainment programs was 50% higher for anophthalmia/microphthalmia (1.9 vs. 1.2) and two‐fold higher for anotia/microtia (2.6 vs. 1.2). Anophthalmia/microphthalmia was more likely than other conditions to co‐occur with other birth defects. All conditions were more frequent among older mothers (40+ years). Conclusions: This data brief provides recent prevalence estimates for anophthalmia/microphthalmia, congenital cataract, and anotia/microtia that address a data gap by examining pooled data from 30 population‐based surveillance systems, covering a five‐year birth cohort of about 12.4 million births.